2017
DOI: 10.1016/j.rser.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the determinants of household electricity prices in the EU: a system-GMM panel data approach

Abstract: A meaningful portion of the consumer basket of European households and companies is embodied by electricity as well as gas or refined petroleum products. As energy products are essential inputs of nearly all final goods and services, whichever change of energy prices has a direct impact of the general price level. In this context, the main purpose of this study is to assess the main drivers of household electricity prices in the European Union (EU), throughout a period of deep sector transformation. Relying on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…The dynamic models introduced a lagged variable as an explanatory variable and introduced instrumental variables by setting moment conditions to handle the autocorrelation of the dependent variables (Blundell and Bond, 1998), which could explore the possible endogeneity of the dependent variables (da Silva and Cerqueira, 2017). The dynamic model used for explaining AMR is shown in Equation (2):…”
Section: Methodsmentioning
confidence: 99%
“…The dynamic models introduced a lagged variable as an explanatory variable and introduced instrumental variables by setting moment conditions to handle the autocorrelation of the dependent variables (Blundell and Bond, 1998), which could explore the possible endogeneity of the dependent variables (da Silva and Cerqueira, 2017). The dynamic model used for explaining AMR is shown in Equation (2):…”
Section: Methodsmentioning
confidence: 99%
“…Presently, research activities focusing on household energy consumption behavior may be classified into three broad categories, including (i) economic, (ii) technological, and (iii) psychological behavior-oriented perspectives (Arawomo, 2017;da Silva and Cerqueira, 2017;Zhou and Yang, 2016). However, several investigations have indicated that the impacts of these procedures are relatively scarce in reality (Wang et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…With the liberalization of the electricity market for households, the opening up of electricity prices to competition on the domestic electricity market was completed in Slovenia. The gradual liberalization has followed a similar path to some other EU and non-EU developed and emerging market economies [11,16,17,25,[38][39][40][41][42][43][44][45][46][47]87,97].…”
Section: Discussionmentioning
confidence: 99%
“…This has economic motives, given that closed national energy markets were incompatible with the concept of a single and competitive economic area. The main reason for sector deregulation was the desire to increase the efficiency of energy undertakings and the energy system as such, as well as to achieve the expected supply-side effects, i.e., lower electricity prices for final consumers [42,43]. The deregulation and liberalization of the electricity market contributed to unleashing entrepreneurial potential in the energy sector.…”
Section: Deregulation and Liberalization Of The Electricity Marketmentioning
confidence: 99%